2012
DOI: 10.1093/brain/aws200
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of protein aggregation and extended phenotyping in filaminopathy

Abstract: Mutations in FLNC cause two distinct types of myopathy. Disease associated with mutations in filamin C rod domain leading to expression of a toxic protein presents with progressive proximal muscle weakness and shows focal destructive lesions of polymorphous aggregates containing desmin, myotilin and other proteins in the affected myofibres; these features correspond to the profile of myofibrillar myopathy. The second variant associated with mutations in the actin-binding domain of filamin C is characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 82 publications
9
94
0
1
Order By: Relevance
“…In this context, the increased expression of chaperones, as observed in plectin-deficient muscle, presumably is a reaction of the cell to facilitate folding of damaged proteins or degradation of aggregated proteins. Similar to what we observed for plectin-related MFM, a predominant localization of chaperones (and of other proteins involved in protein degradation pathways) within protein aggregates has been described for other MFMs, such as filaminopathies (22), myotilinopathies, and desminopathies (23). Most strikingly, highly increased protein levels of HSP27 as well as a tendency for increased αB-crystallin became apparent even during differentiation of plectin-deficient myotubes, indicating that chaperones represented the first line of defense against desmin network aggregation.…”
Section: Figure 10supporting
confidence: 88%
“…In this context, the increased expression of chaperones, as observed in plectin-deficient muscle, presumably is a reaction of the cell to facilitate folding of damaged proteins or degradation of aggregated proteins. Similar to what we observed for plectin-related MFM, a predominant localization of chaperones (and of other proteins involved in protein degradation pathways) within protein aggregates has been described for other MFMs, such as filaminopathies (22), myotilinopathies, and desminopathies (23). Most strikingly, highly increased protein levels of HSP27 as well as a tendency for increased αB-crystallin became apparent even during differentiation of plectin-deficient myotubes, indicating that chaperones represented the first line of defense against desmin network aggregation.…”
Section: Figure 10supporting
confidence: 88%
“…Dysfunctions in protein quality control and protein degradation via the ubiquitin-proteasome system (UPS) and the autophagic-lysosomal pathway seem to play an essential pathogenic role in desminopathy (see [4] for review) and other MFM subtypes [12,36]. Immunolocalization studies in desminopathy, myotilinopathy and filaminopathy demonstrated that abnormal muscle fibers show a markedly increased immunoreactivity for a number of UPS and autophagy proteins [3638].…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, α-B-crystallin and HSP27 are induced during ischemic injury, heat stress, or end-stage failure (Martin et al 1997;Benjamin and McMillan 1998;Knowlton et al 1998;Yoshida et al 1999;Dohke et al 2006). Small HSPs are induced in both myopathic skeletal (Kley et al 2012) and normal muscles after intense exercise (Paulsen et al 2009) and during aging (Doran et al 2007). HSP27 has been shown to preserve cytoskeletal architecture (Mounier and Arrigo 2002) and to play roles in the resistance to oxidative (Huot et al 1996;Dalle-Donne et al 2001), thermal and ischemic stress (Vander Heide 2002;Hollander et al 2004), and to participate in the regulation of cellular redox states (Arrigo 2001) which in turn prevent apoptosis (Mehlen et al 1996) and correlate with hypoxia (Martin et al 1997).…”
Section: Sarcomeric Proteins: Elastic Filamentsmentioning
confidence: 99%